SELECTING CONTROLLERS AND INVERTORS FOR SOLAR CELLS - Xakimov Temurbek Boxodirjon o`g`li; Abdullayev Sherbek Tolibjon o‘g‘li (Лучшие интеллектуальные исследования, 2024)
In this article we are going touch on some of the topics about solar cells, invertors , controllers as well as in what they are more beneficial and at their best sufficiency. Also we are going do discuss what are the advantages and disadvantages of installing solar cells and how much does one need to wait until those cells to pay off. And keeping with that theme we are also going touch on the ways that these devices including invertors, controllers as well as solar cells function.